2013
DOI: 10.1038/srep01653
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Sedimentary Cycles using Autocorrelation of Grain size

Abstract: Detection of sedimentary cycles is difficult in fine-grained or homogenous sediments but is a prerequisite for the interpretation of depositional environments. Here we use a new autocorrelation analysis to detect cycles in a homogenous sediment core, E602, from the northern shelf of the South China Sea. Autocorrelation coefficients were calculated for different mean grain sizes at various depths. The results show that sediments derived from rapid depositional events have a better autocorrelation. Analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Combining the water depth at the coring site and sea-level positions, a paleo-water depth of 30-35 m is estimated when this transgressive sand bed accumulated between 8,300 and 7,300 years of BP. Similar transgressive sandy deposits overlying the Pleistocene terrestrial mud were also found on the middle and outer shelf of the northern SCS (Yim et al, 2006;Xiao et al, 2013;Xiong et al, 2018). These transgressive sands are inferred to be deposited in the inner and middle shelf environments (Figures 6A, B).…”
Section: Postglacial Transgression and Shelf Sedimentationsupporting
confidence: 60%
See 3 more Smart Citations
“…Combining the water depth at the coring site and sea-level positions, a paleo-water depth of 30-35 m is estimated when this transgressive sand bed accumulated between 8,300 and 7,300 years of BP. Similar transgressive sandy deposits overlying the Pleistocene terrestrial mud were also found on the middle and outer shelf of the northern SCS (Yim et al, 2006;Xiao et al, 2013;Xiong et al, 2018). These transgressive sands are inferred to be deposited in the inner and middle shelf environments (Figures 6A, B).…”
Section: Postglacial Transgression and Shelf Sedimentationsupporting
confidence: 60%
“…In the winter, north-easterly waves have an average height of 0.5-4.0 m. High waves are mainly produced by typhoons, which occur during summer and autumn and have a maximum height of over 10 m (Wang, 2007). Typhoon waves in this study area can cause the re-suspension of sea-bottom sediments on the shelf, even on the outer shelf (Xiao et al, 2013;Zhou, 2014).…”
Section: Marine Settingsmentioning
confidence: 80%
See 2 more Smart Citations
“…ESGSC, or end-members, were extracted from the grain size data to identify paleoenvironment and paleoclimate variations. Sediment transport processes and sedimentary environment changes have been previously inferred using the proportions and ranges of grain size components of sediments from the South China Sea (Boulay et al, 2004; Wang et al, 1999; Xiao et al, 2013) and the Arabian Sea (Prins et al, 2000). End-member modelling of grain size data was used to calculate the number of end-members from ESGSC extraction in sediments of the Arabian Sea (Prins et al, 2000).…”
Section: Resultsmentioning
confidence: 99%